IMPACT OF A SUPPORT GROUP FOR THE CAREGIVERS AT AN ORPHANAGE IN TURKEY - Catay, Zeynep; Kologlugil, Dilsad (Wiley, 2017)
This study examined the effectiveness of a 20-session training and supervision support group for caregivers working at an orphanage in Istanbul. The support group's goals were to promote sensitive and responsive caregiving in an institutional setting, to decrease the stress level of the caregivers, and to increase the quality of the relationship between caregivers and children. Thirty-six children (15-37 months) and 24 caregivers participated in this study. Comparison of the pre-and posttest measures of the caregiver intervention and control groups indicated that the intervention yielded successful outcomes. Caregivers in the intervention group displayed significant decreases in the amount of psychological symptoms that they reported and in their emotional burnout levels. Their sense of self-efficacy also improved. In addition, at the end of the 5-month training program, positive developments were observed regarding children's development and problem behaviors. Having regular visitors also was found to be a significant predictor for better developmental outcomes for the children under institutional care.
Keywords: Orphanage; İnstitutional Care; Caregiver Training; Support Group; Turkey; Young-Children; Attachment Disorder; Behavioral-Problems; Institutional Care; Intervention; Infants